2009
DOI: 10.1007/s12265-009-9123-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Intramyocardial Injections of Autologous Bone Marrow Mononuclear Cells in Patients with Ischemic Heart Failure: A Randomized Study

Abstract: Intramyocardial transplantation of autologous bone marrow mononuclear cells (BMMC) is believed to be a promising method for the treatment of patients with chronic ischemic heart disease. The aim of this study was to evaluate long-term results of intramyocardial bone marrow cell transplantation in patients with severe ischemic heart failure. One hundred nine patients with chronic myocardial infarction and end-stage chronic heart failure were randomized into two groups: 55 patients received intramyocardial BMMC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(86 citation statements)
references
References 18 publications
1
84
0
1
Order By: Relevance
“…The primary outcomes of this Where multiple times of follow-up were reported, data were extracted for the longest possible duration of shortterm and long-term follow-up. The authors of 18 trials were contacted for clarification of data, including apparent discrepancies and insufficient detail in the reporting of methods or results 19,[22][23][24][25][26][27][28][29] or for mean and standard deviation values of outcomes where not explicitly reported 11,19,25,[30][31][32][33][34][35][36] or where reported graphically. 9,10,[37][38][39] Responses were obtained from authors of 7 trials (see Acknowledgments section).…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary outcomes of this Where multiple times of follow-up were reported, data were extracted for the longest possible duration of shortterm and long-term follow-up. The authors of 18 trials were contacted for clarification of data, including apparent discrepancies and insufficient detail in the reporting of methods or results 19,[22][23][24][25][26][27][28][29] or for mean and standard deviation values of outcomes where not explicitly reported 11,19,25,[30][31][32][33][34][35][36] or where reported graphically. 9,10,[37][38][39] Responses were obtained from authors of 7 trials (see Acknowledgments section).…”
Section: Data Extractionmentioning
confidence: 99%
“…16 This conclusion was mainly drawn from a combination of low number of events (deaths) from the contributing RCTs and discordant results from one particular study. 19 During the last year, new clinical evidence has become available in the form of new trials of stem cells treatment for HF patients, which have been completed and reported. 9,20,21 In addition, previous meta-analyses have not included trials of cell therapy for DCM.…”
mentioning
confidence: 99%
“…Four relatively larger randomized studies with trans-endocardial application of bone marrow derived MNC or myoblasts have been recently published. Pokushalov's group (Pokushalov et al, 2010) The extremely valuable study comes from Ramshort group. They examined a role of trans-endocardial injections of bone marrow derived MNC into the electrically alive but functionally inactive myocardium in patients with severe, refractory angina and without additional option of revascularization (Ramshort et al, 2009).…”
Section: Transplantation Of Progenitor Cells and Recovery Of LV Functmentioning
confidence: 99%
“…Finaly, and probably the most important aspect of stem cell therapy is a clinical benefit. REPEAR-AMI (Schächinger et al, 2010), studies of Strauer's group in AMI (Yousef et al, 2009) and CMI (Strauer et al, 2010) and the largest study with endocardial implantation of bone marrow derived stem cells in CMI (Pokushalov et al, 2010) have showed clear clinical benefit with hard end points during the relatively long period of follow-up. In our study, we have not a sufficient number of patients to show the difference of major adverse cardiac events in several groups of our patients.…”
Section: Charcteristicsmentioning
confidence: 99%
“…The study of stem cell strategies to address heart failure has advanced steadily over the last decade, predominantly in the adult population. There is expanding clinical experience with first generation cell-based therapies to mitigate the effects of ischemic and nonischemic heart diseases in adults that involve the administration of both autologous and allogeneic bone marrow-derived stem cells (BMSCs) [1][2][3][4][5][6]. These studies have provided evidence that validates the overall safety and feasibility of direct injection into the left heart muscle in adult cardiac disease.…”
Section: Introductionmentioning
confidence: 99%